2013
DOI: 10.1371/journal.pbio.1001513
|View full text |Cite
|
Sign up to set email alerts
|

An Abscisic Acid-Independent Oxylipin Pathway Controls Stomatal Closure and Immune Defense in Arabidopsis

Abstract: In Arabidopsis the stomatal defense response, a feature of the innate immunity in plants, involves oxylipin-mediated mechanisms that are independent of the phytohormone abscisic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
232
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 232 publications
(253 citation statements)
references
References 74 publications
(98 reference statements)
15
232
1
5
Order By: Relevance
“…By contrast, our findings consistently show that under no circumstances are equal concentrations of ABA and MeJA similarly potent in stomatal closure. The ability of MeJA to induce stomatal closure remains controversial, because in support of our data, a recent report showed that MeJA at concentrations up to 100 mM is ineffective in reducing stomatal aperture (Montillet et al, 2013). Furthermore, dose response curve studies show that maximum reduction of stomatal aperture is achieved by 12-OPDA at approximately 5-fold-lower concentrations than that of MeJA (Fig.…”
Section: External Application Of 12-opda Promotes Stomatal Closuresupporting
confidence: 75%
See 1 more Smart Citation
“…By contrast, our findings consistently show that under no circumstances are equal concentrations of ABA and MeJA similarly potent in stomatal closure. The ability of MeJA to induce stomatal closure remains controversial, because in support of our data, a recent report showed that MeJA at concentrations up to 100 mM is ineffective in reducing stomatal aperture (Montillet et al, 2013). Furthermore, dose response curve studies show that maximum reduction of stomatal aperture is achieved by 12-OPDA at approximately 5-fold-lower concentrations than that of MeJA (Fig.…”
Section: External Application Of 12-opda Promotes Stomatal Closuresupporting
confidence: 75%
“…Asterisk denotes significant difference in aperture under a given treatment (P , 0.0001). 12-OPDA in reducing stomata aperture is also reported as a functional innate immunity mechanism to ward plants against pathogens (Montillet et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…9-HOT and 9-KOT induce ROS or act as reactive electrophile species to trigger transcriptional reprogramming or to modify macromolecules covalently (Vellosillo et al, 2007;Mueller et al, 2008;López et al, 2011;Vicente et al, 2012;Farmer and Mueller, 2013;Montillet et al, 2013). Plant responses to these oxylipins are under mitochondrial retrograde control, as 9-HOT causes mitochondrial aggregation and loss of mitochondrial membrane potential and NOXY2 (and the 9-LOX signaling NOXY genes DYNAMIN-RELATED PROTEIN3A/NOXY15 and FRIENDLY MITOCHONDRIA/NOXY38) encodes a mitochondrial protein (Vellosillo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies in Arabidopsis (Arabidopsis thaliana) showed a 9-LOX function in activating local defense and stomata closure against virulent Pseudomonas spp. (Hwang and Hwang, 2010;López et al, 2011;Montillet et al, 2013) as well as 9-LOX and a-DOX pathway cooperation in triggering systemic resistance (Vicente et al, 2012). There is also evidence of a role in activating systemic defense for C9 oxylipins formed by nonenzymatic free radical reactions (Jung et al, 2009;Wang et al, 2014;Wittek et al, 2014).…”
mentioning
confidence: 99%
“…Stomatal aperture was measured on epidermal peels excised from the abaxial side of leaves of 3-to 4-week-old plants, essentially as described by Montillet et al (2013). In all cases, two epidermal peels from two independent plants of the indicated genotype were first incubated for 30 min in darkness at ambient air in a bathing solution containing 30 mM KCl, 1 mM CaCl 2 , and 10 mM MES/Tris pH6.0, prior to exposure to the indicated treatment.…”
Section: Measurements Of Stomatal Aperturementioning
confidence: 99%